CLINICAL-EPIDEMIOLOGICAL PROFILE OF OCCURRENCES RELATED TO CLINICAL CAUSES IN THE MOBILE EMERGENCY CARE SERVICE (SAMU) IN ANÁPOLIS, GOIÁS, IN THE FIRST QUARTER OF 2023 (CIPEEX, 2025)
The Mobile Emergency Care Service (SAMU) is responsible for urgent care, including clinical causes, which are prevalent among the cases attended by this service. OBJECTIVE: This study aimed to characterize the clinical and epidemiological profile of clinical cause-related attendances, identifying the number of occurrences, the locations of origin, the relationship with days of the week and time of day, and highlighting the main clinical reasons for care during the first quarter of 2023. METHODOLOGY: A descriptive, cross-sectional, and retrospective epidemiological study was conducted using data from Anápolis, Goiás. Data were collected from SAMU attendance records. RESULTS: Analysis revealed 2,739 occurrences of clinical causes, with January having the highest number of attendances. Regarding sociodemographic data, there was a prevalence of care for women in January and March and for men in February, with the highest number corresponding to individuals over 60 years old. Most occurrences originated at home throughout the study period. Additionally, the most prevalent time of day was the afternoon in January and March, and nighttime in February. Regarding days of the week, the highest number of occurrences was on Monday in January, Wednesday in February, and Saturday in March. The most common symptoms were general discomfort and abdominal pain, falls from standing height, among others. The most frequent destination was the Emergency Care Unit (UPA).
Keywords: Mobile Emergency Care Service; SAMU; General Symptoms; Epidemiological Studies; Pre-Hospital Services